2022
DOI: 10.3390/antiox11040780
|View full text |Cite
|
Sign up to set email alerts
|

Creeping Wood Sorrel and Chromium Picolinate Effect on the Nutritional Composition and Lipid Oxidative Stability of Broiler Meat

Abstract: The study investigates the efficacy of Cr in broilers, aiming to evaluate the effects of Chromium picolinate (CrPic) in association with creeping wood sorrel powder (CWS) on the proximate composition, fatty acids profile, bioactive nutrients and lipid oxidative stability of broiler meat. A total of 120 Cobb 500 chickens were assigned into three treatments: a control diet (C) and two test diets, including 200 µg/kg diet CrPic (E1), and 200 µg/kg diet CrPic +10 g CWS/kg diet (E2). Dietary supplementation with Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…Nevertheless, vitamin E was poorly deposited in the breast and thigh meat of chickens fed T1 and T2 treatments compared to T0. Similar results were reported by [ 25 ] when Cr was supplemented in combination with creeping wood sorrel in chicken diets. However, other authors [ 68 ] showed that the vitamin E content of sea buckthorn fruit oil had no significant effect on the depostion in rat livers and attributed this effect to the high individual variability of the biological response between the animals used.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, vitamin E was poorly deposited in the breast and thigh meat of chickens fed T1 and T2 treatments compared to T0. Similar results were reported by [ 25 ] when Cr was supplemented in combination with creeping wood sorrel in chicken diets. However, other authors [ 68 ] showed that the vitamin E content of sea buckthorn fruit oil had no significant effect on the depostion in rat livers and attributed this effect to the high individual variability of the biological response between the animals used.…”
Section: Discussionsupporting
confidence: 90%
“…The fatty acid profile obtained from the chemical analysis (as g/100 g fatty acid methyl esters) was used to determine several nutritional quality indices of meat lipids. Nutritional quality indices of meat lipids were assessed by calculating the PUFA n-6/PUFA n-3, Σ PUFA/Σ MUFA ratio, atherogenicity index (IA), thrombogenicity index (IT), saturation index (SI), the ratio of hypocholesterolemic and hypercholesteremic fatty acids (h/H), and the health-promoting index (HPI) as previously described [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lutein and zeaxanthin content in liver was significantly lower in the experimental groups compared to C group. In contrast, the results of a previous study (Saracila et al, 2022) performed under normal temperature showed an increased content of lutein and zeaxanthin in breast and thigh samples from chickens fed a diet supplemented with Cr and CWS. However, the total antioxidant capacity recorded in the liver was significantly higher in group Cr-VC, Cr-Zn and Cr-CWS compared to C. These observations indicate that vitamin C and Zn supplementation have led to increased antioxidant capacity in the liver.…”
Section: Resultscontrasting
confidence: 78%
“…The creeping wood sorrel plants were harvested from Ilfov county in their late vegetative stage, slow dried and grounded. Plant samples were characterized previously by Saracila et al, (2022) that revealed important concentration of crude protein (16.74%), crude fibre (19.36%) and ash (22.56%), high concentration of lutein and zeaxanthin (267.41µg/g) and vitamin E (210.93µg/g) with a high total antioxidant capacity (170.70 µM Trolox).…”
Section: Experiments Designmentioning
confidence: 99%